The characteristics of organized sport and physical activity initiatives for older adults in Sweden - Helena Ericson; Susanna Geidne (Frontiers Media S.A., 2023)
There is a common understanding that sport and physical activity can be important to address healthy aging. There are individual-level recommendations about how much physical activity people of different ages should engage in to gain health benefits, but at the same time there are no recommendations for how organizations should organize physical activities to suit as many people as possible for as long as possible. The purpose of this study was to explore the characteristics of sport and physical activity initiatives that older adults participate in. Different ongoing sport and physical activity initiatives that involve older adults were investigated regarding their focus, organization, intensity and organizer, and in relation to their costs, booking opportunities and recruitment. The study was conducted with a cross-sectional design using the Salutogenic Physical Activity Health Resources Questionnaire (SPAHRQ). The study included 27 different initiatives with 372 participants (60% women) ranging from 60 to 96 years of age. A health-promoting, salutogenic settings-based approach, and specifically the concepts drop-in, drop-through and drop-over were used in discussing recommendations for the organization of sport and physical activity for older adults. The main findings were that who organizes the sport and physical activity initiative seems to affect the characteristics of how it is organized and what characterizes the participants in it. Despite the differing characters of sport and physical activity initiatives, the majority of older adults are recruited by internal contacts like friends and family. Which older adults participate in which initiatives is explained mostly by the age and gender of the participants. In conclusion, to attract as many older adults as possible, organizations should work with lowering the thresholds, as well as within and between, organizations, and raise the threshold for dropping out of sports and physical activity.